Analysis of Factors Influencing The Decline in Public Transportation Interest in Timika City - Hira Wahyu; Tri Wahyuni; Fitriani Jum Hamdana; Yahya Nusa (CV. Publikasi Indonesia, 2024)
This research aims to determine the factors influencing the reduction of public transportation in Timika City. The method used is quantitative, which is collecting data through questionnaires. The research results show that several factors influencing the reduction in public transportation in Timika City are limited accessibility, service, and comfort. The analysis used in this research is multiple linear regression analysis. The results of this research explain that variable X1, namely accessibility, and variable X2, namely service, have a positive and insignificant influence on the interest of public transport users. Meanwhile, variable X3, namely comfort, has a positive and significant effect on the interest of public transport users. The implications of this study show that increasing comfort is the most significant factor in attracting public interest in using public transportation in Timika City. Improvements in accessibility and quality of service, while important, are not enough without increased convenience. Effective strategies should focus on improving hygiene, seat comfort, in-vehicle temperature, and tranquility during the trip.